2014
DOI: 10.1002/jmv.24082
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus seroprevalence among hemodialysis and hemophiliac patients in Tunisia (North Africa)

Abstract: The aims of this study are to determine seroprevalence of Hepatitis E virus (HEV) in Tunisian blood donors and to evaluate its risk of parenteral transmission. Sera collected from 426 blood donors were tested for HEV IgG by indirect ELISA. Individuals were recruited from two national transfusion centers, in the North and the South of the country. Seroprevalence of HEV IgG was then compared with two other groups with increased risk of exposure to parenterally transmitted agents: 80 hemophiliac and 286 hemodialy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(42 reference statements)
1
11
1
Order By: Relevance
“…Generally, reported seroprevalences are much higher in Egypt than in Morocco or Tunisia, where reported seroprevalence rates do not exceed 46% in older adults. In Northern Tunisian regions, by using the Globe Diagnostics assay, reported seroprevalences were 12;1% among pregnant women [7], 28.9% among polytransfused patients [7], 10.2% among hemodialysis patients [6] and 4,5% among blood donors [6]. A similar low prevalence of 5.4% was reported among blood donors by using the Genelabs Diagnostics assay [8].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Generally, reported seroprevalences are much higher in Egypt than in Morocco or Tunisia, where reported seroprevalence rates do not exceed 46% in older adults. In Northern Tunisian regions, by using the Globe Diagnostics assay, reported seroprevalences were 12;1% among pregnant women [7], 28.9% among polytransfused patients [7], 10.2% among hemodialysis patients [6] and 4,5% among blood donors [6]. A similar low prevalence of 5.4% was reported among blood donors by using the Genelabs Diagnostics assay [8].…”
Section: Discussionmentioning
confidence: 66%
“…A number of studies have described the prevalence of enterically transmitted hepatitis viruses in various parts of Tunisia [6] [79]. However, there are no data from the Southern governorates.…”
Section: Introductionmentioning
confidence: 99%
“…The flow diagram of the study selection is shown in Figure and Figure S8. We identified 31 studies from 17 countries between 1994 and 2016 that met the selection criteria . One of the identified publications (Dalekos et al) was considered as two studies as it presented data emanating from two regions in Greece, making the total count of analysed studies included in the meta‐analysis 32.…”
Section: Resultsmentioning
confidence: 99%
“…For many years, hepatitis E was recognized as an infection of tropical countries, especially developing and undeveloped countries, caused by contaminated drinking water and food. In developed countries, HEV infection was thought to be travel associated, but many studies reported autochthonous cases (3)(4)(5).…”
Section: Contextmentioning
confidence: 99%